Corporate Finance Legal Protection as a Recipient Fiduciary Warranties Made Object of Evidence in Criminal Problem - Tegar Firmansyah (Jurnal Daulat Hukum, 2018)
. In a consumer financing agreement in the form of a motor vehicle then the finance company will carry out the object binding fiduciary insurance for motor vehicles which have been delivered to the consumer. Fiduciary purpose vehicle that has been delivered to the consumer is to secure the creditor on the agreements that have been made of the risk of a breakdown of installments or transferred vehicle that has been tied with the fiduciary guarantee. Mastery of objects that remain in the possession of the debtor could be used to commit a crime which causes fiduciary object used as evidence in court and until the court decision object was confiscated by the state guarantee. The research is qualitative research in the form of descriptive analysis using normative juridical approach. Legal protection against creditors under Article 20 of Act No. 42 Of 1999 regarding Fiduciary stating fiduciary fixed object fiduciary assurance follow wherever located or when objects are on the fiduciary third party then the lender has the authority to take it. Article contains the principle Droite de Suite. The legal consequences of confiscation by the state that is the position of the objects belong to the state and the object can not be used by anyone. Deprivation of fiduciary objects do not cause the voidance of fiduciary so that the debtor shall replace objects fiduciary pursuant to Article 1131 Civil Law Book.Keywords: Legal Protection; Fiduciary; Corporate Financing; Equipment Evidence.